KEBERLANJUTAN DAN KONTRIBUSI INDUSTRI KECIL KERAJINAN GENTENG DALAM MENINGKATKAN KESEJAHTERAAN PENGRAJIN DAN MASYARAKAT: (Studi Kasus Industri Genteng Desa Winong kecamatan Maospati Kabupaten Magetan) - Harry Nurhadi (Universitas Darul Ulum, 2021)
Tile is a framework part of a house or building that has a function as a house cover from all kinds of weather and is a small industry that needs to be preserved. The purpose of this study was to find out how the efforts of tile craftsmen in maintaining the sustainability of the small tile craft industry and to find out how much the tile industry's contribution in improving the welfare of craftsmen and the community. This type of research is field research or field research. (Arikunto, 2005) with a descriptive qualitative research paradigm with a location in Winong Village, Maospati District, Magetan Regency. This research was conducted in February – June 2021. With the subject of tile craftsmen, the village government and the community with a sample of 20 craftsmen, respondents were taken based on the characteristics of the income level received with different amounts. Disproportionate stratified random sampling technique was used to determine the number of samples. In the analysis of data analysis through three components Data Reduction, Data Display and Conclusion Drawing/verification. in maintaining the sustainability of the tile industry, namely by maintaining aspects: capital, raw materials, marketing, technology, labor. These aspects must be maintained so that the tile industry can survive until now. 2) What is the contribution of the small tile craft industry in the welfare of the craftsmen and their communities? The number of labor absorption from the tile industry in Winong village has increased from year to year, as well as increasing the morning income of owners and workers and 3) The tile industry is able to bring changes for craftsmen towards prosperity both in terms of income, settlement/housing, clothing, health and nutrition, better education.